Cost-benefit analysis of esophageal cancer endoscopic screening in high-risk areas of China - Yang, Juan (Baishideng Publishing Group Co., Limited, 2012)
AIM: To estimate the cost-benefit of endoscopic screening strategies of esophageal cancer (EC) in high-risk areas of China. METHODS: Markov model-based analyses were conducted to compare the net present values (NPVs) and the benefit-cost ratios (BCRs) of 12 EC endoscopic screening strategies. Strategies varied according to the targeted screening age, screening frequencies, and follow-up intervals. Model parameters were collected from population-based studies in China, published literatures, and surveillance data. RESULTS: Compared with non-screening outcomes, all strategies with hypothetical 100 000 subjects saved life years. Among five dominant strategies determined by the incremental cost-effectiveness analysis, screening once at age 50 years incurred the lowest NPV (international dollar-I$55 million) and BCR (2.52). Screening six times between 40-70 years at a 5-year interval [i.e., six times(40)f-strategy] yielded the highest NPV (I$99 million) and BCR (3.06). Compared with six times(40)f-strategy, screening thrice between 40-70 years at a 10-year interval resulted in relatively lower NPV, but the same BCR. CONCLUSION: EC endoscopic screening is cost-beneficial in high-risk areas of China. Policy-makers should consider the cost-benefit, population acceptance, and local economic status when choosing suitable screening strategies.